2017
DOI: 10.1049/mnl.2017.0192
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of superparamagnetic iron oxide nanoparticles with tunable size: from individual nanoparticles to nanoclusters

Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs) have a wide variety of biomedical applications. Synthesis of SPIONs with well-defined, tunable size in a facile way is highly desirable. In this work, a one-pot polyol method was developed for preparation of SPIONs with tunable size and high quality in the presence of poly (acrylic acid) (PAA). By adjusting the amount of PAA used, the isolated nanoparticles and nanoparticle clusters were able to be synthesised. As-synthesised nanoparticles and nanoclusters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Following the work of Mi et al 30 showing that the addition of PAA can yield clustered IONPs, the synthesis was also performed in the presence of PAA in a range of different concentrations (0.02−0.1 M). The experimental procedure (with PAA) is shown in step 1 and 2 in Figure 6.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the work of Mi et al 30 showing that the addition of PAA can yield clustered IONPs, the synthesis was also performed in the presence of PAA in a range of different concentrations (0.02−0.1 M). The experimental procedure (with PAA) is shown in step 1 and 2 in Figure 6.…”
Section: ■ Methodsmentioning
confidence: 99%
“…The influence of poly­(acrylic acid) (PAA) concentration over the magnetic and structural properties of IONPs for the coprecipitation method has previously been reported. , Mi et al showed that for the thermal decomposition of Fe­(acac) 3 in polyol, the increase of PAA concentration would contribute mostly at coating the particles, as the chance of a PAA molecule binding with multinanocrystal nuclei could be enhanced.…”
Section: Introductionmentioning
confidence: 99%